Influências das condições meteorológicas na armazenabilidade de grãos de milho em unidades armazenadoras convencionais - Baptista, Caio Gustavo da Silva (2024)
During the storage of agricultural grains, in a natural environment, grains may experience weight loss due to technical breakdown and loss or gain of weight resulting from moisture breakdown, as the grain mass is constantly subjected to internal and external factors. The temperature and relative humidity of the ambient air, as well as natural drying and aerobic respiration of the grains, are factors that interfere with storage quality. Understanding, throughout grain storage, the quantitative losses or gains of stored grains and the interaction effects of meteorological conditions on these losses or gains has strategic importance for managers of Storage Units and for the National Supply Company (CONAB), by offering technical information to support their decision-making, regarding the development of policies aimed at grain storage and the management of public stocks. CONAB, within its official network of Storage Units, allows up to 0.005% per day as the maximum technical breakdown of the stored mass, regardless of grain types, physical characteristics, or local climatic conditions. When it comes to moisture breakdown, water content levels are analyzed upon entry and exit of grains from the Storage Unit. Thus, the present proposal aimed to evaluate, in corn grains, the quantitative losses or gains, corresponding to technical breakdown and moisture breakdown, and the possible relationships between the daily average ambient air temperature (°C) and daily average relative humidity of the ambient air (%) with the daily total moisture breakdown of grains (Kg) during storage in 10 conventional CONAB Storage Units, in various Brazilian states, over a period of approximately 5 years. Data collection for corn grains was conducted using the SAAGRA software. Meteorological data were obtained using the INMET online platform. Data organization and interpretation occurred through descriptive statistics, and Microsoft Power BI Desktop was used for graphical panel elaboration and correlation assessment. After analyzing the databases, it can be affirmed that: 1) an error was identified in the SAAGRA software, recorded in the CLF, related to duplicated data of corn grain technical breakdown (Kg); 2) the long storage period and the value of 0.005% of maximum daily technical breakdown justified its higher value over moisture breakdown; 3) corn grains maintained physical quality even with a long storage period, with a maximum water content of 13.00%; 4) manual recording in the SAAGRA software of grain water content (%) at the product's exit from the Storage Unit showed repetition of entries; 5) there is need for update on the CONAB Organization Norm (NOC), No. 30.512, regarding grain moisture breakdown, mentioning the natural and measurable weight gain due to its hygroscopic nature; 6) variation in ambient air temperature (°C) did not justify a reduction or increase in corn grain moisture breakdown (Kg); and 7) variation in ambient air relative humidity (%) did not justify a reduction or increase in corn grain moisture breakdown (Kg).